Ensiklopedi Centhini - Dwiyanto, Djoko, 1953- (Pilahan, Yogyakarta : Panji Pustaka, 2008)
Adaptation of Serat Centini, a classical Javanese epic poetry
Keywords: Javanese literature; Epic poetry, Javanese